Voices of teenage transplant survivors : miracle-like - Sample, Susan J. (Emerald Publishing Limited, 2021)
While the physical and emotional trials of waiting on transplant lists are featured in popular media, the struggles recipients face years after surgery are not. 'Voices of Teenage Transplant Survivors' introduces illness narratives from an unrecognized patient population: recipients of heart, liver, and kidney transplants. Offering unique narratives by adolescents who use poetry to explore issues surrounding the changing body, independence, identity, and mortality, the book showcases a message of healing and voices of hope amid uncertainty. Illuminating the physical, psychological, and existential challenges confronted by adolescents for which organ rejection and side effects loom in their future, Sample details the poetry workshops where these adolescents articulated experiences silenced by family, friends, and the culture of medicine. She includes close readings and analyses of their writings, along with writing prompts and references to narrative medicine theory. This powerful book offers something new for medical and health professionals, medical humanities researchers, students, and the public.